2023
DOI: 10.3390/medicina59030483
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Prostate Cancer and Urinary Tract Infections: A New Perspective of Prostate Cancer Pathogenesis

Abstract: Background and objectives: Microbiota of the urinary tract may be associated with urinary tract malignancy, including prostate cancer. Materials and Methods: We retrospectively collected patients with newly diagnosed prostate cancer and subjects without prostate cancer from the National Health Insurance Research Database (NHIRD) in Taiwan between 1 January 2000 and 31 December 2016. A total of 5510 subjects were recruited and followed until the diagnosis of a primary outcome (urinary tract infection, pyeloneph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Urine reflux has been proposed as a cause of chronic inflammation in the prostate due to chemical irritation resulting from the accumulation of uric acid. Several studies have demonstrated that uric acid is the primary chemical compound involved in this type of damage [96]. Notably, the hereditary risk of PCa is greater than that of any other human cancer [93].…”
Section: Origins Of Inflammationmentioning
confidence: 99%
“…Urine reflux has been proposed as a cause of chronic inflammation in the prostate due to chemical irritation resulting from the accumulation of uric acid. Several studies have demonstrated that uric acid is the primary chemical compound involved in this type of damage [96]. Notably, the hereditary risk of PCa is greater than that of any other human cancer [93].…”
Section: Origins Of Inflammationmentioning
confidence: 99%